2015
DOI: 10.1159/000442048
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study Showing an Excellent Response of Patients with Low-Risk Differentiated Thyroid Cancer Who Did Not Undergo Radioiodine Remnant Ablation after Total Thyroidectomy

Abstract: ment, measuring Tg and making a WBS. The patients were then annually monitored with neck US and Tg measurement under TSH between 0.5 and 2.0 mIU/l for 36-84 months. Results: Neck US of all patients, 3 months after TT, presented no evidence of abnormal residual tissues or metastatic lymph nodes (negative neck US); at this time, the mean Tg level was 0.42 ng/ml. Six months after surgery, after rhTSH, the mean thyroid bed uptake was 1.82%, and Tg levels ranged from 0.10 to 22.30 ng/ml (mean, 2.89 ng/ml). The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Current second generation Tg assays (0.05-0.1 ng/mL) have shown that patients with lowrisk DTC with undetectable baseline Tg rarely recur (5). In this sense, study published in 2016 by Janovsky (1) concluded that an excellent response to treatment can be confirmed by the trend of Tg and US, these being the best follow-up approaches, showing that the use of RRA only to achieve negative levels of Tg for surveillance is not necessary because it is not an isolated value, but the tendency of Tg during follow-up, the determining factor for both (1). Therefore, based on the above, it should be emphasized that the trend of Tg is highly suggestive of being a predictor of disease-free follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current second generation Tg assays (0.05-0.1 ng/mL) have shown that patients with lowrisk DTC with undetectable baseline Tg rarely recur (5). In this sense, study published in 2016 by Janovsky (1) concluded that an excellent response to treatment can be confirmed by the trend of Tg and US, these being the best follow-up approaches, showing that the use of RRA only to achieve negative levels of Tg for surveillance is not necessary because it is not an isolated value, but the tendency of Tg during follow-up, the determining factor for both (1). Therefore, based on the above, it should be emphasized that the trend of Tg is highly suggestive of being a predictor of disease-free follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…O ver the last decades, the incidence of DTC has increased significantly, especially of tumors smaller than 2 cm (1)(2)(3). Despite this, most of these patients have an excellent prognosis and a long followup during their lifetime (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…26 Several studies show that undetectable postoperative Tg levels correspond with a low incidence of recurrence, while elevated Tg levels are associated with recurrence. 27,28 Rosario and colleagues demonstrated that Tg levels often detected recurrent papillary thyroid carcinoma, even prior to structurally detectable disease on ultrasound. 29 One study evaluating the risk of recurrent PTC demonstrated an increase in Tg more than twofold was seen in 80% of patients with recurrence and only 13% of patients without demonstrable recurrent PTC on imaging.…”
Section: Assessing the Adequacy Of Surgical Resectionmentioning
confidence: 99%
“…On one hand, the majority of patients with recently detected DTC have PTMC, which is associated with excellent prognosis and, in general, no mortality. For these diseases, appropriate risk stratification to determine which cancers require specific treatment and ongoing continuous restratification are essential to avoid overtreatment (17). For a specifically selected subgroup of low-risk patients, simple surveillance, with no specific treatment, has been proposed and stimulated (12)(13)(14).…”
mentioning
confidence: 99%